Stakeholders meeting on scaling the homegrown school feeding program through chicken eggs in Yirgalem, Sidama Region - Yemane, Tsion; Argaw, Amare (International Livestock Research Institute, 2025)
Various agriculture sector stakeholders explored collaborative efforts, shared insights and developed actionable plans to enhance the Homegrown School Feeding Program’s impact on Sidama Region schools and communities. They discussed strategies for expanding the program in the Sidama Region, emphasizing incorporating chicken eggs as a key component of the feeding initiative.